Draft Annual Plan 1988-89 Volume-I Notes Government of Andhra Pradesh - Planning Commission (Planning Commission, 1988)
Given the imperatives of the growth with equity and the need to provide immediate and long term relief from drought, a plan of Rs.1558.41 crores has been proposed for 1988-89, broad details of which are given below. While compulsions for a plan of this size are obvious, the resources on hand (which are estimated at Rs.1017.51 crores) do fall short of the plan requirements. The success of the plan, therefore, depends on the extent this gap can be bridge through additional resources mobilisation at the State level and additional assistance from the Centre.
Government of Andhra Pradesh, Finance and Planning (Planning Wing) Department